Comparative Pharmacognostic Evaluation of Leaves of Citrus sinensis Var. Jaffa and Citrus paradisi var. Redblush - Sohi, Shaheena; Shri, Richa (Pharmacognosy Communications)
Background: The genus Citrus (family: Rutaceae), a native to South East Asia and China, comprises aromatic shrubs and trees which are highly ac- knowledged by folk medicine of various tropical tribes and cultures and also by modern science for the treatment of various ailments. Citrus sinen- sis var. jaffa and Citrus paradisi var. redblush are two medicinally important members of this genus. However, the first step in utilization of a medicinal plant is authentication which involves pharmacognostic examination of the plant material. Systematic pharmacognostic studies for leaves of these Citrus species have not yet been done. Objective: To study and compare pharmacognostic profile of leaves of Citrus sinensis var. jaffa and Citrus paradisi var. redblush. Methods: Leaves were subjected to detailed macro- scopic, microscopic (qualitative and quantitative), physiochemical, fluores- cence and preliminary phytochemical analysis as per standard pharmaco- poeial procedures and WHO guidelines. Results: Macroscopic examination showed that leaves of the two species can be differentiated based on na- ture of petiole, size and shape. Diagnostic microscopic features including the size of the epidermal cells, the type of stomata, stomatal index and lo- cation of secretory cavities help to distinguish the two species. Results for physiochemical and fluorescence analysis were recorded which will serve as reference standards. Preliminary phytochemical screening showed the presence of alkaloids, flavonoids, tannins, saponins, steroids, volatile oils, proteins and sugars. Conclusion: Pharmacognostic standards for leaves have been generated for the first time. These may prove useful to establish identity, quality and purity of these medicinally important Citrus species.
Keywords: Citrus; Fluorescence; Leaf; Microscopic; Physiochemical; Phy- tochemical.